Apoplastic invasion patterns triggering plant immunity: plasma membrane sensing at the frontline. (28th July 2019) - Schellenberger, Romain; Touchard, Matthieu; Clément, Christophe; Baillieul, Fabienne; Cordelier, Sylvain; Crouzet, Jérôme; Dorey, Stéphan
Summary: Plants are able to effectively cope with invading pathogens by activating an immune response based on the detection of invasion patterns (IPs) originating from the pathogen or released by the plant after infection. At a first level, this perception takes place at the plasma membrane through cell surface immune receptors and although the involvement of proteinaceous pattern recognition receptors (PRRs) is well established, increasing data are also pointing out the role of membrane lipids in the sensing of IPs. In this review, we discuss the evolution of various conceptual models describing plant immunity and present an overview of well‐characterized IPs from different natures and origins. We summarize the current knowledge on how they are perceived by plants at the plasma membrane, highlighting the increasingly apparent diversity of sentinel‐related systems in plants.